Internet-Based Education: A New Milestone for Formal Language and Automata Courses - Rocha, João E. M. [UNESP]; Olivete, Celso [UNESP]; Gomes, Pedro H. A. [UNESP]; Garcia, Rogério E. [UNESP]; Correia, Ronaldo C. M. [UNESP]; de Souza, Gabriel Spadon [UNESP]; Eler, Danilo M. [UNESP] (Springer Nature, 2018)
This paper aims at introducing a methodology focused on student-centered learning and aided by an educational collaborative and graphical tool. Through it, we enable students to interact with abstract topics as well as interact with each other. Our motivation was the lack of capability to represent knowledge and abstractions faced by students that work alone. In this regard, we present as result a tool to be used in the whole educational processes, together with a teaching-learning methodology that is described from multiple points of view.
Keywords: Automata Theory; Empirical analysis; Formal Languages; Learning tool; Teaching methodology